Human capital formation with heterogeneous agents, sustainable debt policies and growth: Who benefits from fiscal policy rules? - Fabienne Dascher-Preising; Alfred Greiner (Bielefeld University, Faculty of Business Administration and Economics, 2021)
With this paper our objective is to study the effects of different deficit policies in an endogenous growth model with publicly funded human capital accumulation and public debt, where we allow for heterogeneous households. Two types of households are considered. One household acquires human capital or skills through education while the other household remains low-skilled. Aggregate production is given by a function with physical capital and labor as input factors, where total labor input is modeled by a CES function with high-skilled and low-skilled labor as arguments. The government can run into debt, but, the primary surplus is a positive function of public debt which guarantees that public debt is sustainable. We study the characteristics and stability of the steady state and we investigate the effects of fiscal policy with regard to long-run growth and the distribution of welfare of the two households. Further, we analyze growth and welfare effects of switching from a balanced government budget to permanent public deficits taking into account transition dynamics.
urn:nbn:de:0070-pub-29568842
Keywords: E62; H52; H63; I28; J24; 330; Human capital; heterogeneous agents; distribution; endogenous economicgrowth; fiscal policy; sustainable public debt